Multicystic renal dysplasia: a diagnostic dilemma. (12th May 2011) - Alam, Kiran; Varshney, Manoranjan; Aziz, Mehar; Maheshwari, Veena; Basha, Mahfooz; Gaur, Kavita; Ghani, Imran
Abstract : A 3-year-old male child had left-sided abdominal lump for 4 months. Radiological examination revealed a cystic mass in the left kidney. A tentative diagnosis of multicystic nephroma was made on clinical and radiological examination. Cytology was inconclusive. Nephrectomy was done. A final diagnosis of multicystic dysplasia was made on histological examination.